Clinical and molecular epidemiology of Acinetobacter baumannii bloodstream infections in an endemic setting. (March 2017) - Marchaim, Dror; Levit, Dana; Zigron, Roy; Gordon, Michal; Lazarovitch, Tsillia; Carrico, Joao A; Chalifa-Caspi, Vered; Moran-Gilad, Jacob
Aim: The transmission dynamics of Acinetobacter baumannii in endemic settings, and the relation between microbial properties and patients' clinical outcomes, are yet obscure and hampered by insufficient metadata.Methods & Results: Of 20 consecutive patients with A. baumannii bloodstream infection that were thoroughly analyzed at a single center, at least one transmission opportunity was evident for 85% of patients. This implies that patient-to-patient transmission is the major mode of A. baumannii acquisitions in health facilities. Moreover, all patients who died immediately (<24 h of admission) were infected with a single clone (ST457; relative risk = 1.6; p = 0.05).Conclusion: This preliminary analysis should prompt further investigation by mapping genomic virulence determinants among A. baumannii ST457 lineage compared with other strains.